Social representation of mental health of young adults post- pandemic of COVID-19 - Beathriz Costa Dourado, Lorena; Sena Carvalho, Valéria (Revista de Psicologia, 2024)
The COVID-19 pandemic brought transformations, among them, changes related to social, economic and psychological instability, resulting from the fear of infection and social isolation, caused the worsening of mental health issues, especially among young adults who are in situation of social vulnerability. This study aimed to analyze the social representations of the mental health of young adults in situations of social vulnerability after the pandemic, identify psychosocial impacts and describe ways of coping with the problems experienced during the pandemic. 20 users, aged 18 to 29, were interviewed from a CRAS in the city of Teresina-PI. The results showed that participants understand mental health as a state of well-being, on the other hand, others understand mental health as the absence of psychological problems. Psychosocial impact factors were identified: grief and losses, negative feelings, difficulties in adapting to the context, mental problems and task overload. Self-care, a support network, professional help and work were the strategies developed by young adults during a pandemic. It is clear that social representations around the topic are addressed by different social and individual dimensions, in this case the COVID-19 pandemic.